Electric-dipole absorption resonating with longitudinal optical phonon-plasmon system and its effect on dispersion relations of interface phonon polariton modes in metal/semiconductor-stripe structures. (4th December 2017) - Sakamoto, Hironori; Takeuchi, Eito; Yoshida, Kouki; Morita, Ken; Ma, Bei; Ishitani, Yoshihiro
Abstract: Interface phonon polaritons (IPhPs) in nano-structures excluding metal components are thoroughly investigated because they have lower loss in optical emission or absorption and higher quality factors than surface plasmon polaritons. In previous reports, it is found that strong infrared (IR) absorption is based on the interaction of p-polarized light and materials, and the resonance photon energy highly depends on the structure size and angle of incidence. We report the optical absorption by metal/semiconductor (bulk-GaAs and thin film-AlN)-stripe structures in THz to mid-IR region for the electric field of light perpendicular to the stripes, where both of s- and p-polarized light are absorbed. The absorption resonates with longitudinal optical (LO) phonon or LO phonon-plasmon coupling (LOPC) modes, and thus is independent of the angle of incidence or structure size. This absorption is attributed to the electric dipoles by the optically induced polarization charges at the metal/semiconductor, heterointerfaces, or interfaces of high electron density layers and depression ones. The electric permittivity is modified by the formation of these dipoles. It is found to be indispensable to utilize our form of altered permittivity to explain the experimental dispersion relations of metal/semiconductor-IPhP and SPhP in these samples. This analysis reveals that the IPhPs in the stripe structures of metal/AlN-film on a SiC substrate are highly confined in the AlN film, while the permittivity of the structures of metal/bulk-GaAs is partially affected by the electric-dipoles. The quality factors of the electric-dipole absorption are found to be 42–54 for undoped samples, and the value of 62 is obtained for Al/AlN-IPhP. It is thought that metal-contained structures are not obstacles to mode energy selectivity in phonon energy region of semiconductors.